Flipbook Maker is an Electronic Learning Media for Social Studies Subjects - Subiyakto, Bambang; Jumriani, Jumriani; Syaharuddin, Syaharuddin; Rusmaniah, Rusmaniah; Triyono, Sigit; Jannah, Fathul (Universitas Lambung Mangkurat, 2024)
Technology integration in learning is essential in this digital era to improve student interaction and understanding. This community service aims to develop and implement Flipbook Maker as an electronic learning media for Social Sciences (IPS) subjects. The methods used in this community service activity include the planning, training, implementation, and evaluation stages. First, a needs analysis was conducted to determine the material to be presented as a flipbook. Second, IPS teachers were given intensive training on integrating Flipbook Maker into the curriculum.Furthermore, the flipbooks that had been created were tested in several classes to see their effectiveness and student responses. The activity results showed that using Flipbook Maker as an electronic learning medium can increase student interest, facilitate material delivery, and enrich learning resources. The evaluation showed that most students felt more motivated and helped understand IPS material. Thus, Flipbook Maker can be an alternative and innovative learning media for IPS subjects.